Experiences of underrepresented faculty in pediatric emergency medicine. (28th January 2021) - Nfonoyim, Bianca; Martin, Ashley; Ellison, Angela; Wright, Joseph L.; Johnson, Tiffani J.
Abstract: Objective: The aim of this study is to elucidate the unique challenges faced by pediatric emergency medicine (PEM) physicians from racial/ethnic groups underrepresented in medicine (URiM). Methods: This study is a subanalysis of data from 18 URiM faculty from a sample of 51 semistructured key informant interviews with PEM faculty in the top NIH‐funded pediatric departments and highest‐volume pediatric EDs in the country. Faculty are from eight hospitals representing a spectrum of geographic locations including the northeastern, midwestern, western, and southern regions of the country. Results: Of 18 study participants, the majority were Black (72.2%) and female (83.3%). Three main thematic categories were identified: challenges related to race, support systems, and suggested strategies to improve diversity and inclusion in PEM. A common race‐related experience was microaggressions from colleagues and patients. Additionally, when attempting to lead and assert themselves, URiM women in particular were perceived as "angry" and "intimidating" in a way that non‐URiM peers were not. As a result of these negative experiences, participants described the need to go above and beyond to prove themselves. Such pressure produced stress and feelings of isolation. Participants combatted these stressors through resilience strategies such as formal mentorship and peer and family support. Participants indicated the need to increase diversity and create more inclusive work environments, which would benefit both URiM physician wellness and the diverse patients they serve. Conclusion: Those URiM in PEM face subtle racial discrimination at an institutional, peer, and patient level. The stress caused by this discrimination may further contribute to physician burnout in PEM. While URiMs adopt individual resilience strategies, their unique challenges suggest the need for departmental and institutional efforts to promote greater diversity and inclusion for physician wellness, retention, and quality patient care.